Komunikasi Politik Kepala Desa dalam Mendorong Inovasi Pembangunan Desa: Studi Kasus Tiga Desa di Lereng Gunung Ungaran, Jawa Tengah - Arumsari, Nugraheni; Septina, Wenny Eka; Luthfi, Muhammad; Rizki, Nur Kholis Ali (Jurnal Politik Indonesia: Indonesian Political Science Review, 2017)
Communication is a strategy to deliver information to the public and medium to develop a good will in citizen both human and infrastructure development. Good communication must be acquired by many stakeholders of the citizen in all hierarchy of the government; one of them is the village headman. The village headman as a stakeholder of the village is required to be able to interact properly in term of communication and village development. Innovation and ideas about latest development cannot run properly without good communication between village headman, community leaders and villagers. This study investigated the communication style done by the village headman. It was conducted in village Kalisidi, Gonoharjo and Diwak. As the result, there are some communication style done in these villages among stake holders and the citizen. They are: (1) A direct approach to the society (informal communication to village communities); (2) Approach among Village Community Institutions (communication group of community and communication networks); (3) Public Communication by using Social Media, and (4) Public Information Board as a medium to inform village annual budget as a form of transparency and socialization of village resort and rural education movement.